Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12986-020-00491-7
|View full text |Cite
|
Sign up to set email alerts
|

Systemic vitamin intake impacting tissue proteomes

Abstract: The kinetics and localization of the reactions of metabolism are coordinated by the enzymes that catalyze them. These enzymes are controlled via a myriad of mechanisms including inhibition/activation by metabolites, compartmentalization, thermodynamics, and nutrient sensing-based transcriptional or post-translational regulation; all of which are influenced as a network by the activities of metabolic enzymes and have downstream potential to exert direct or indirect control over protein abundances. Considering m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 237 publications
(277 reference statements)
1
13
0
1
Order By: Relevance
“…The presented application of the Breast Cancer Proteome Portal is focused on metabolic networks because nutrient status regulates protein expression, which, in turn, regulates cellular metabolism , and drives tumorigenesis; , a theme reinforced by findings that the metabolome and proteome independently stratify tumors according to clinical classification . However, the scope and utility of the Breast Cancer Proteome Portal extends to all cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…The presented application of the Breast Cancer Proteome Portal is focused on metabolic networks because nutrient status regulates protein expression, which, in turn, regulates cellular metabolism , and drives tumorigenesis; , a theme reinforced by findings that the metabolome and proteome independently stratify tumors according to clinical classification . However, the scope and utility of the Breast Cancer Proteome Portal extends to all cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-oxidative and anti-inflammatory activities of adlay can be attributed to the flavonoids and various polyphenols in adlay bran [ 11 , 29 ]. In addition, whole-grain foods are dietary sources of nutrients that may potentially affect various metabolic processes [ 30 ], and thus, the replacement of daily staple foods with dehulled adlay, containing 3–5 times the vitamin B and E of polished rice according to the Taiwan Food Composition Databases, may have some beneficial effects on regulating metabolic disorders. A study demonstrated that ethanolic extracts in adlay bran inhibited reactive oxygen species (ROS) and pro-inflammatory substance production in vitro [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The failure to meet micronutrient requirements is important give their varied roles impacting protein metabolism. Numerous enzymes impacted by vitamin co-factors, can influence protein expression, by virtue of their ability to act as antioxidants, nuclear receptor agonists, and signal transducers [ 31 ] Second , the prevalence of PEW among patients on MHD in KFHRI was estimated at 18% (24% and 11% among males and females, respectively). Prior to our study, PEW amongst HD patients in Bangladesh has not been given importance in terms of being a health issue.…”
Section: Discussionmentioning
confidence: 99%